Investigation among students’ and teachers’ perception of climate health awareness regarding low carbon ecofriendly practices - Natalia, Maryam; Ullah, Waheed; Khan, Ahsan Riaz; Wahid, Abdul; Mehmood, Muhammad Sajid; Naz, Madeeha (Frontiers in Environmental Science, 2023)
Introduction: Global climate change has become rapidly one of humanity’s most pressing environmental concerns. To overcome this issue, public environmental awareness, sustainable behavior and understanding must be increased. Method: So, this study explored the awareness of climate change, perception and attitude towards nature, impacts, effects, hopes, responsibility and engagement in low carbon behavior among students (n = 500) and faculty members (n = 50) from universities in Multan city. Data was collected using questionnaire from non-environmental science departments (n = 6). Descriptive statistics and Pearson correlation were used to compile the results. Findings: Results concluded that awareness of climate change is higher in teachers than students. Both respondents showed similar responses regarding their perception of issues, and impacts but showed discrepancy while selecting effects of climate change. Participants’ attitudes towards the environment and hope for mitigation are similar. Students and teachers believed that every sector has major responsibility except teachers agreed on full individual responsibility and international organization has a small portion of responsibility. Both participants showed no interest in engagement in low carbon activities. Conclusion: It is imperative that colleges and universities invest in educational programs and sustainability initiatives in order to shape the attitudes and behaviors of students and faculty members towards environmental sustainability.